High temperature fatigue tests of notched specimens made of titanium Grade 2. (April 2015) - Gallo, P.; Berto, F.; Lazzarin, P.
Highlights: Data from uniaxial fatigue tests on notched specimens made of titanium Grade 2 are summarized. The tests are performed at room temperature and 500 °C. Commercially Pure (CP) titanium Grade 2. Two geometries are considered: semicircular notches and plates weakened by symmetric V-notches. The results are re-analyzed by means of the mean value of the Strain Energy Density (SED). Abstract: The present paper summarizes data from uniaxial-tension load controlled fatigue tests on notched specimens made of titanium Grade 2. The tests are performed at room temperature and 500 °C that, having regard to the properties of titanium Grades 2, can be considered as a limit temperature. Indeed, in the final application, a component can be intentionally or unintentionally pushed to the limit. Commercially Pure (CP) titanium Grade 2 is employed for high-performance applications, such as jet engine and airframe components (e.g. ductwork, brackets), or small rolls for hot-rolling of metals, and it is subjected, in service, to a combination of mechanical and moderate thermal loadings that under uncontrolled conditions can become very important. Two geometries are considered: semicircular notches and plates weakened by symmetric V-notches, with opening angle and tip radius being equal to 90° and 0.75 mm, respectively. The present work is motivated by the fact that, at the best of authors' knowledge, no results seem to be available for notched components tested at high temperature made of titanium Grade 2. After a brief literature review of the recent works available for titanium in general, the Grade 2 is introduced in the "material" section. Subsequently, the experimental procedure is described in detail and the new fatigue data are summarized in terms of stress range, at the considered temperatures. Finally, the results are re-analyzed by means of the mean value of the Strain Energy Density (SED) and the advantages of the method are pointed out.